Enhancing Web Programming Education: A Data Mining Approach to Feasibility Prediction through Project-Based Learning - Kurniadi, Denny (Universitas Negeri Padang, 2023)
This research explores the integration of Project-Based Learning (PBL) in web programming education, focusing on predicting the feasibility of an inventory item application through data mining techniques. Emphasizing student-centered instruction and collaboration, the study aims to assess the impact of PBL on student engagement, knowledge, and skill development. Employing a carefully designed evaluation system, the research anticipates contributing valuable insights into the effectiveness of PBL in teaching web programming. Specific data mining methods employed will be highlighted, and anticipated findings will be discussed. PBL and provide insights into the effectiveness of PBL in teaching web programming subjects.